P073 RISK STRATIFICATION TO INCREASE VENOUS THROMBOEMBOLISM PROPHYLAXIS IN PEDIATRIC INFLAMMATORY BOWEL DISEASE. (7th February 2019) - Levine, Anne E; Chi, Lisa Y; Sobczyk, Patricia; Bousvaros, Athos; Trenor, Cameron C; Zitomersky, Naamah
Abstract: Objectives: Pediatric patients with inflammatory bowel disease (IBD) are at increased risk of venous thromboembolism (VTE), but are often overlooked for pharmacologic prophylaxis. We instituted a risk-stratification algorithm to identify high-risk patients and offer enoxaparin prophylaxis (EP) aimed at preventing VTE in hospitalized children with IBD flares. Methods: We performed a prospective observational quality improvement and patient safety initiative at a large pediatric tertiary care hospital from September 2012 to June 2017. Major risk factor was admission for IBD flare with colonic involvement. Minor risk factors were personal history of thrombosis, first-degree family history of VTE, known thrombophilia, persistent anti-phospholipid antibody >12 weeks, oral contraceptive use, smoking, obesity, thalidomide use, or central venous catheter. The algorithm was incorporated into the electronic medical record (EMR). Results: 458 patients aged 1-27 years (mean 14.6 years, 58.4% male) were admitted 787 times. The electronic risk-stratification algorithm was applied to 234 (29.7%) admissions. Of those, 29 (12.4%) met high-risk criteria and received prophylactic enoxaparin. Forty-three admissions were not screened in the EMR but received VTE prophylaxis, indicating likely use of the posted paper algorithm. Patients assessed with the electronic tool were more likely to receive prophylactic enoxaparin than those who were not screened (p < 0.05). There were 8 total VTE events (7 venous, 1 arterial), 3 of whom were receiving EP. There were no bleeding complications in patients receiving EP. Conclusions: A standardized approach to risk-stratification and EP is important in preventing thrombotic events in pediatric patients with IBD. Risk assessment using our EMR algorithm increased the number of patients who receive thromboprophylaxis. EP is safe for children with active IBD flares.